Servus or Pater? How Paradoxical Intent Can Qualify Leadership: Inductions from the Kingdom of Bhutan. Issue 3 (3rd July 2022) - Sousa, Milton; Cunha, Miguel Pina E.; Simpson, Ace V.; Giustiniano, Luca; Rego, Arménio; Clegg, Stewart
ABSTRACT: We offer a set of conceptual distinctions between servant and paternalistic leadership, which we support with a new model that further extends the notion of paradoxical dynamic equilibrium. We used an in-depth case study of narratives on servant and paternalistic leadership from the Kingdom of Bhutan's transition to democratic leadership. These narratives are rich in paradoxical tensions from which we extrapolate our findings. From our inductive documentary analysis, we establish that servant and benevolent paternalistic leadership perform genuine concern for the wellbeing of followers. However, while servant leaders seemingly promote centrifugal forces of change, humility and broader inclusion of others as followers, paternalistic leaders (both benevolent and exploitative), focus on the centripetal forces of stability, unquestioned authority and exclusion of those that do not follow and thus are outside their direct protection. As outlined in our circular model of paradoxical intent, distinguishing servant leadership and paternalistic leadership can be understood through distinct splitting and integration processes between the poles of main and utilitarian intent. MAD statement The concept of servant leadership seems to be increasingly adopted by organizations. This is a welcoming development given its potential contribution to address today's social and environmental challenges, as expressed in the UN Sustainable Development Goals. However, there is a risk that leaders carelessly appropriate the term without sufficiently understanding its unique characteristics and implications. Servant leadership can, for instance, be easily confused with paternalistic leadership. This article aims to clarify the distinctions between these two models and contribute to a more conscious adoption and development of servant leadership in organizations.